Experimental use of alcohol in early adolescence: the 11-year follow-up of the 1993 Pelotas (Brazil) birth cohort study Uso experimental de álcool no início da adolescência: a visita de 11 anos da coorte de nascimentos de Pelotas, Rio Grande do Sul, Brasil, 1993 - Ricardo B. Noal; Ana M. B. Menezes; Cora Luiza Araújo; Pedro C. Hallal (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2010)
The aim of this study was to estimate the prevalence of experimental alcohol intake and associated factors in early adolescence. The overall sample consisted of 4,452 adolescents (mean age = 11.3 years; SD = 0.3) from the 1993 birth cohort in Pelotas, Rio Grande do Sul State, Brazil. Experimental use of alcohol was reported by 17.5% of the interviewees (95%CI: 16.3-18.6), and 5% reported having tried alcohol at nine years of age or younger. Prevalence of experimental alcohol use was higher among adolescents whose mothers had consumed alcohol during pregnancy, whose parents consumed alcohol, who worked outside the home themselves, and who had ever tried smoking. Family strife, parental alcohol intake, and adolescent smoking were strong predictors of experimental alcohol use in early adolescence. Special attention should be targeted to these groups in order to avoid heavy and premature alcohol use in early adolescence. Este trabalho teve como objetivo avaliar a prevalência de uso experimental de bebidas alcoólicas e fatores associados no início da adolescência. Compuseram a amostra 4.452 adolescentes (média = 11,3 anos; DP = 0,3) da coorte de nascimentos de 1993 de Pelotas, Rio Grande do Sul, Brasil. O uso experimental de álcool foi referido por 17,5% dos entrevistados (IC95%: 16,3-18,6) e 5% referiram ter experimentado com nove anos ou menos. O risco de uso experimental de álcool foi maior nos adolescentes cujas mães referiram ter bebido na gestação, quando ambos os pais usavam bebidas alcoólicas, entre os adolescentes que trabalhavam fora e naqueles que já experimentaram cigarro ou outras drogas. As relações familiares, o uso de álcool pelos pais, e o tabagismo do adolescente são os fatores fortemente associados ao uso experimental de álcool no início da adolescência. Mais atenção deveria ser dada especialmente a esses grupos, a fim de combater o consumo precoce de álcool.